Single Crystalline 4H-SiC MEMS Devices with N-P-N Epitaxial Structure. Issue 1693 (18th June 2014) - Zhao, Feng; Lim, Allen; Chen, Zhibang; Huang, Chih-Fang
ABSTRACT: In this paper, single crystal 4H-SiC MEMS devices with n-p-n epitaxial structure was fabricated. A dopant-selective photoelectrochemical etching technique was applied to etch the sacrificial p-type SiC layer to release n-type SiC suspended structures on n-type SiC substrate. The selective etching was achieved by applying a bias which employs the different flat-band potentials of n-SiC and p-SiC in KOH solution. Such MEMS devices have the potential to fully exploit the superior properties of single crystal SiC for harsh environment operation, as well as mature epitaxial growth and device fabrication of 4H-SiC. The n-p-n structure, together with the previously reported p-n structure, extends the capability of monolithic integration between MEMS with electronic devices and circuits on SiC platform.